Land use and economic changes around EDSA-MRT stations in Quezon City - Lapena, Mary Therese T. (2004)
Any transportation project has economic and land use impacts along its corridor. For modes with specific terminals or stations, the effects are most prominent in the vicinity of these stations. This is because stations or terminals are considered points of convergence of people and therefore provides a captured market for economic activities.
The thesis entitled "Land Use and Economic Changes Around EDSA-MRT Stations in Quezon City" gives attention to land use, land value and economic impacts of one of the few urban rail systems in the Philippines, the EDSA-MRT. The main objective of the study is to identify the land use and economic activity changes brought about by the construction of the EDSA-MRT on parcels of land in the vicinity of the Quezon Avenue and GMA-Kamuning Stations. The study compared the land use and intensity of activities in the study areas before (1995) and after (2003) the EDSA-MRT construction; traced a pattern of land use change in the study areas; and assessed whether the changes in land use, land value and economic environment in the study are were attributable to the MRT.
The results of the study revealed that the changes which occurred around the MRT stations involved changes in the type of economic activity for which the land is used. These changes in land use and economic activity are limited to parcels in the immediate vicinity of the stations and along paths of commuters, as the MRT has only been in operation for three (3) years.
Increased land use intensity and economic activity were observed on land along the path of pedestrians going to and coming from MRT Stations. Businesses which opened in those lots include fast food chains and eateries, convenience stores and small retail shops. These are businesses whose markets are the pedestrians and passengers of the MRT.
It is too soon to observe widespread changes in land use and value for land due to MRT stations in the study area. At present, the more significant factors which influence how land is utilized are those infrastructures which have been there for a longer time. These infrastructures include the EDSA, Quezon Avenue and Timog Avenue and establishments such as ABS-CBN.
It is recommended that policies and plans be put in place soon as major developments around MRT Stations are anticipated. A well-designed plan should be enforced to prevent disorderly development that will result to aesthetically and functionally poor station areas.
Thesis (M.S. Civil Engineering)--University of the Philippines, Diliman.
Keywords: Street-railroads -- Economic aspects -- Philippines -- Quezon City; Local transit stations -- Philippines -- Quezon City; Land use -- Philippines -- Quezon City